Adjustable FAU / LTA (CuⅠ) zeolite nanocrystal, preparation method and use thereof

Through a low-cost and environmentally friendly preparation method, efficient and stable FAU/LTA (CuⅠ) zeolite nanocrystals were successfully synthesized, solving the problems of complex and low synthesis in the prior art, and achieving industrial production of nanocrystals and excellent performance of CO adsorbents.

CN116282062BActive Publication Date: 2025-04-08DALIAN UNIV OF TECH PANJIN INST OF IND TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310318126.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-28
Publication Date
2025-04-08
Estimated Expiration
2043-03-28

AI Technical Summary

Technical Problem

The existing FAU/LTA zeolite nanocrystal synthesis methods have complex processes, low synthesis efficiency, difficult to separate nanomolecular sieves, require a large number of structural guides and mineralizers, high synthesis costs, and serious environmental pollution, which limits its industrial production and application.

Method used

The preparation method with small water volume, low cost and low environmental pollution is adopted. Through the steps of full mixing of silicon, aluminum and alkali sources, steam-assisted aging and crystallization treatment, washing, drying and calcining, adjustable FAU/LTA (CuⅠ) zeolite nanocrystals are prepared, and their structure and performance are further optimized through solid grinding and calcining with rare earth metal salts and copper salts.

Benefits of technology

It has achieved efficient synthesis of FAU/LTA (CuⅠ) zeolite nanocrystals, with a yield of more than 90%, a uniform particle size and good stability, suitable for industrial production, and has good performance in the field of CO adsorbents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116282062B_ABST
    Figure CN116282062B_ABST
Patent Text Reader

Abstract

The present invention provides an adjustable FAU / LTA (CuⅠ) zeolite nanocrystal, a preparation method and use thereof. The preparation method of the adjustable FAU / LTA (CuⅠ) zeolite nanocrystal of the present invention is as follows: sodium hydroxide, a silicon source, an aluminum source and water are mixed to prepare a mixture; the mixture is subjected to aging and crystallization treatment in sequence under steam-assisted conditions to obtain a crystalline product. After grinding with a rare earth metal salt and a reducing acid and vacuum drying, the mixture is solid-state ground with a cuprous salt and placed in a tubular furnace, and calcined in the presence of a protective gas to obtain an adjustable FAU / LTA (CuⅠ) zeolite nanocrystal. The adjustable FAU / LTA (CuⅠ) zeolite nanocrystal of the present invention uses a small amount of water in the synthesis process, and the prepared adsorbent has good stability. In addition, the present invention also has the advantages of low cost, low environmental pollution, and being conducive to industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to molecular sieve technology, in particular to an adjustable FAU / LTA (CuⅠ) zeolite nanocrystal, a preparation method and application thereof. Background Art

[0002] Faujasite (FAU) and Linde-type zeolite (LTA) are two of the most important zeolites due to their wide commercial applications. From the perspective of framework structure, both FAU and LTA zeolites are composed of stacked sodalite cages. For FAU zeolite, the sodalite cages are linked together by double six-membered rings to form large cavities called super cages. While for LTA zeolite, the sodalite cages are linked together by double four-membered rings to form alpha cages. Both zeolites can be synthesized from the Na2O–Al2O3–SiO2–H2O system using tetramethylammonium cations (TMA) as structure-directing agents. Studies have shown that TMA, which is almost the same size as the sodalite cage, can induce the formation of some porous structures or secondary structural units of zeolites, and there can be only one TMA cation in one sodalite cage. Some inorganic ions, such as small alkali metal ions (Na and Li), are hydrated in the synthesis solution. They can accommodate water molecules like a network and also have a structure-directing effect. It is known that the crystallization of FAU and LTA is sensitive to synthesis parameters, such as sodium concentration, silicon / aluminum ratio and aging time. Usually, small changes in these parameters will change the composition of the product. Composite zeolites are becoming more and more important, and some composite zeolites, such as β / MCM-41, ZSM-5 / Y and MAZ / ZSM-5, show obvious synergistic effects in catalysis. FAU and LTA form an interaction of competing kinetic and thermodynamic factors. It also makes it show different advantages over single zeolites in adsorption and catalysis.

[0003] FAU and LTA molecular sieves are widely used in catalysis, separation, ion exchange and other fields. The products obtained by existing preparation technology are mostly porous materials with a particle size of more than 1μm. Molecular sieves of this particle size cannot effectively exert their unique pore characteristics, especially in the application of catalysis and adsorption. Molecular sieves with the following characteristics can obtain better adsorption and catalytic performance: (1) Larger external specific surface area can obtain more active centers; (2) Reducing particle size is conducive to the diffusion of reactants and products, making the catalyst more efficient and ion exchange more likely to occur; (3) More pore openings make it difficult for reactants to block the pores, which is conducive to extending the catalyst operation cycle and making ion exchange more fully carried out in the pores.

[0004] Although there are technologies for synthesizing FAU / LTA zeolite nanocrystals, the synthesis methods have technical defects to varying degrees, such as complex process, low synthesis efficiency, difficulty in separating and collecting nano-molecular sieves from mother liquor, the need for a large amount of structure-directing agents and mineralizers, high synthesis cost, and large amounts of waste liquid discharged to pollute the environment. This greatly limits the industrial production and application of FAU / LTA zeolite nanocrystals. Therefore, it is of great significance and value to develop a green and simple synthesis route for FAU / LTA zeolite nanocrystals. Summary of the invention

[0005] The purpose of the present invention is to propose a method for preparing adjustable FAU / LTA (CuⅠ) zeolite nanocrystals in view of the problems of complex process and low synthesis efficiency in the prior art. The method has small water consumption, low cost, small environmental pollution, and is conducive to industrial production. The adsorbent prepared by the present invention has good stability.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing adjustable FAU / LTA (CuⅠ) zeolite nanocrystals, comprising the following steps:

[0007] Step 1, fully mix the silicon source: aluminum source: alkali source (calculated as hydroxide): water in a molar ratio of 1:0.2-1.2:0.1-4:5-100 to prepare a mixture;

[0008] Step 2: Under steam-assisted conditions, the mixture is subjected to aging and crystallization treatments in sequence to obtain a crystalline product;

[0009] Step 3, washing, drying and calcining the crystal product in sequence to obtain FAU / LTA type zeolite nanocrystals;

[0010] Step 4, mixing the FAU / LTA zeolite nanocrystals and the rare earth metal salt M in a solid phase, and vacuum drying to obtain a solid mixture A containing rare earth elements, wherein the mass ratio of the FAU / LTA zeolite nanocrystals to the rare earth metal salt is 1:0.01-3;

[0011] Step 5, solid-state grinding the solid mixture A and the cuprous salt, wherein the mass ratio of the FAU / LTA zeolite nanocrystals to the cuprous salt is 1:0.4-1, to obtain a solid mixture B containing the cuprous salt;

[0012] Step 6: placing the solid mixture B in a tubular furnace and calcining it in the presence of a protective gas to obtain adjustable FAU / LTA (CuⅠ) zeolite nanocrystals.

[0013] Furthermore, the silicon source in step 1 is one or more of white carbon black, porous silicon, solid silica gel and silica sol.

[0014] Furthermore, the aluminum source in step 1 is one or more of aluminum isopropoxide, sodium aluminate, aluminum hydroxide, aluminum chloride and aluminum sulfate.

[0015] Furthermore, the alkali source in step 1 is one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, magnesium hydroxide, ammonia water and ethylenediamine. The alkali source is preferably sodium hydroxide.

[0016] Furthermore, the preferred molar ratio of the silicon source: the aluminum source: the alkali source (calculated as hydroxide): water is 1: 0.2-1.2: 0.1-4: 5-50.

[0017] Furthermore, step 2, under steam-assisted conditions, sequentially aging and crystallizing the mixture specifically comprises the following steps: transferring the mixture into an open glass container, and then transferring the glass container into a hydrothermal reactor liner, adding 1-20 ml of deionized water to the reactor liner, and preventing water outside the glass container from entering the glass container; aging the mixture at a temperature of 20 to 70° C. and under steam-assisted conditions, the aging time is 0 to 12 days, and the preferred aging time is 0 to 5 days; the crystallization treatment temperature is 20 to 120° C., and the crystallization time is 0 to 8 days, and the preferred crystallization treatment temperature is 50 to 100° C., and the crystallization time is 6 to 50 hours.

[0018] Furthermore, the calcination in step 3 is carried out in an air atmosphere, the calcination temperature is 240-550° C., and the calcination time is 3-12 hours.

[0019] Furthermore, a reducing acid may be added to the solid mixture A in step 4, and the mass ratio of the reducing acid to the FAU / LTA (CuⅠ) type zeolite nanocrystals is 0.01-2.4:1, and the preferred mass ratio is 0.2-1.2:1.

[0020] Furthermore, the reducing acid is one or more of citric acid, oxalic acid, sulfurous acid and phosphorous acid.

[0021] Furthermore, the rare earth metal salt M in step 4 is one or more of lanthanum nitrate, cerium nitrate, cerium trichloride, lanthanum chloride, cerium acetate and lanthanum acetate.

[0022] Furthermore, the solid phase mixing and stirring time in step 4 is 0.15-24 hours, preferably 0.5-4 hours.

[0023] Furthermore, the drying in step 4 is: drying in a vacuum drying oven at 60-200° C. for 12-72 hours; preferably, the drying is drying in a vacuum drying oven at 70-120° C. for 18-24 hours.

[0024] Furthermore, the cuprous salt in step 5 is one or more of cuprous chloride, cuprous bromide, cuprous nitrate, cuprous carbonate, cuprous sulfate and cuprous acetate.

[0025] Furthermore, the grinding time in step 5 is 0.5-8 hours, preferably 0.5-3 hours.

[0026] Furthermore, in step 6, the calcination temperature is 120-600° C., and the calcination time is 4-36 hours. Preferably, the calcination temperature is 400-600° C., and the calcination time is 5-24 hours.

[0027] Furthermore, the protective gas in step 6 is one or more of nitrogen, helium and argon.

[0028] Another object of the present invention is to disclose an adjustable FAU / LTA (CuⅠ) zeolite nanocrystal prepared by the above method.

[0029] The FAU / LTA (CuⅠ) zeolite nanocrystalline CO adsorbent is used to separate and purify CO, wherein the FAU / LTA (CuⅠ) zeolite nanocrystalline CO adsorbent is pressed into tablets and sieved to 20 to 40 meshes before adsorption evaluation.

[0030] Another object of the present invention is to disclose the use of adjustable FAU / LTA (CuⅠ) zeolite nanocrystals in the field of CO adsorbent.

[0031] The adjustable (size-adjustable) FAU / LTA (CuⅠ) zeolite nanocrystals, preparation methods and uses thereof of the present invention have the following advantages compared with the prior art:

[0032] 1) The preparation method of the present invention has high synthesis efficiency, and the yield of adjustable FAU / LTA (CuⅠ) zeolite nanocrystals reaches more than 90%.

[0033] 2) The preparation method of the present invention uses less water, has low cost, and causes less environmental pollution, which is conducive to industrial production.

[0034] 3) The adjustable particle size of the FAU / LTA (CuⅠ) zeolite nanocrystals of the present invention is about 100-200 nm, and the particle size distribution is uniform and has good stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is the XRD pattern of the FAU / LTA (CuⅠ) zeolite nanocrystals prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0036] The present invention is further described below in conjunction with embodiments:

[0037] Comparative Example 1

[0038] Step 1: Dissolve 0.721 g of sodium hydroxide in 33 mL of water, add 1.61 g of sodium aluminate and stir magnetically for 30 min, then add 2.3 g of white carbon black to prepare a mixture.

[0039] Step 2, transfer the above mixture into an open glass container, then transfer the glass container into the liner of a hydrothermal reactor, add 10 ml of deionized water into the liner, and prevent water outside the glass container from entering the glass container; age the mixture at 25°C under steam-assisted conditions for 3 days; then heat the hydrothermal reactor to 80°C, and crystallize the mixture under steam-assisted conditions for 8 hours to obtain a crystalline product.

[0040] Step 3: The crystallized product is centrifugally washed for 3 times, dried at 50° C. for 8 hours, and calcined in a muffle furnace at 400° C. for 4 hours to obtain FAU / LTA type zeolite nanocrystals.

[0041] Example 1

[0042] Step 1: Dissolve 1.248 g of sodium hydroxide in 16.5 mL of water, add 1.12 g of sodium aluminate and stir magnetically for 30 min, then add 1.15 g of white carbon black to prepare a mixture.

[0043] Step 2, transfer the above mixture into an open glass container, then transfer the glass container into the liner of a hydrothermal reactor, add 10 ml of deionized water into the liner, and prevent water outside the glass container from entering the glass container; age the mixture at 25°C under steam-assisted conditions for 3 days; then heat the hydrothermal reactor to 100°C, and crystallize the mixture under steam-assisted conditions for 9 hours to obtain a crystalline product.

[0044] Step 3: The crystal product is centrifuged and washed three times, and dried at 50°C for 8 hours to obtain FAU / LTA zeolite nanocrystals.

[0045] Step 4: Add 0.2 g of cerium nitrate to the crystal product and grind it in the solid state for 10 min, then add 0.25 g of citric acid and continue grinding for 20 min. Dry it in a vacuum drying oven at 100° C. for 12 hours.

[0046] Step 5: solid-state grinding the dried product with 3 g of cuprous chloride for 30 min to obtain a solid mixture containing cuprous salt.

[0047] Step 6: Place the solid mixture in a tubular furnace and calcine at 400° C. for 6 hours in the presence of nitrogen to obtain an adjustable FAU / LTA (CuⅠ) zeolite nanocrystal.

[0048] like Figure 1 The product is well crystallized, without amorphous phase, and the peak position corresponds to the standard FAU and LTA zeolite spectra. There are no impurity peaks other than FAU and LTA, and no other zeolite impurity phases. And due to the small particle size of the product, the XRD spectrum has a broad flower phenomenon, FAU / LTA (CuⅠ) zeolite nanocrystals.

[0049] Example 2

[0050] Step 1: Dissolve 1.1 g of magnesium hydroxide in 15 mL of water, add 1.12 g of sodium aluminate and stir magnetically for 30 min, then add 1.1 g of white carbon black to prepare a mixture.

[0051] Step 2, transfer the above mixture into an open glass container, then transfer the glass container into the liner of a hydrothermal reactor, add 10 ml of deionized water into the liner, and prevent water outside the glass container from entering the glass container; age the mixture at 25°C under steam-assisted conditions for 3 days; then heat the hydrothermal reactor to 100°C, and crystallize the mixture under steam-assisted conditions for 8 hours to obtain a crystalline product.

[0052] Step 3: The crystallized product is centrifuged and washed three times, and dried at 50° C. for 8 hours to obtain FAU / LTA zeolite nanocrystals.

[0053] Step 4: Add 0.15 g of cerium nitrate to the crystal product and grind it in the solid state for 10 min, then add 0.2 g of citric acid and continue grinding for 20 min. Dry it in a vacuum drying oven at 120° C. for 12 hours.

[0054] Step 5: solid-state grinding the dried product with 2.58 g of cuprous chloride for 30 min to obtain a solid mixture containing cuprous salt.

[0055] Step 6: Place the solid mixture in a tubular furnace and calcine at 400° C. for 6 hours in the presence of nitrogen to obtain an adjustable FAU / LTA (CuⅠ) zeolite nanocrystal.

[0056] Example 3

[0057] Step 1: Dissolve 1.1 g of sodium hydroxide in 5 mL of water, add 0.71 g of sodium aluminate and stir magnetically for 30 min, then add 1.1 g of white carbon black to prepare a mixture.

[0058] Step 2, transfer the above mixture into an open glass container, then transfer the glass container into the liner of a hydrothermal reactor, add 10 ml of deionized water into the liner, and prevent water outside the glass container from entering the glass container; age the mixture at 25°C under steam-assisted conditions for 3 days; then heat the hydrothermal reactor to 80°C, and crystallize the mixture under steam-assisted conditions for 16 hours to obtain a crystalline product.

[0059] Step 3: The crystal product was centrifuged and washed three times, and dried at 50°C for 12 hours to obtain FAU / LTA zeolite nanocrystals.

[0060] Step 4: Add 0.25 g of cerium nitrate to the crystal product and grind it for 10 min, then add 0.32 g of citric acid and continue grinding for 20 min. Dry it in a vacuum oven at 120°C for 12 hours.

[0061] Step 5: solid-state grinding the dried product with 0.4 g of cuprous chloride for 30 min to obtain a solid mixture containing cuprous salt.

[0062] Step 6: Place the solid mixture in a tubular furnace and calcine at 400° C. for 6 hours in the presence of nitrogen to obtain an adjustable FAU / LTA (CuⅠ) zeolite nanocrystal.

[0063] Example 4

[0064] Step 1: Dissolve 0.28 g of calcium hydroxide in 15 mL of water, add 2.21 g of sodium aluminate and stir magnetically for 30 min, then add 1.15 g of white carbon black to prepare a mixture.

[0065] Step 2, transfer the above mixture into an open glass container, then transfer the glass container into the liner of a hydrothermal reactor, add 10 ml of deionized water into the liner, and prevent water outside the glass container from entering the glass container; age the mixture at 25° C. under steam-assisted conditions for 3 days; then heat the hydrothermal reactor to 80° C., and crystallize the mixture under steam-assisted conditions for 20 hours to obtain a crystalline product.

[0066] Step 3: The crystal product was centrifuged and washed three times, and dried at 50°C for 24 hours to obtain FAU / LTA zeolite nanocrystals.

[0067] Step 4: Add 0.31 g of cerium nitrate to the crystal product and grind it for 10 min, then add 0.3 g of citric acid and continue grinding for 20 min. Dry it in a vacuum oven at 120°C for 12 hours.

[0068] Step 5: solid-state grinding the dried product with 0.5 g of cuprous chloride for 30 min to obtain a solid mixture containing cuprous salt.

[0069] Step 6: Place the solid mixture in a tubular furnace and calcine at 400° C. for 6 hours in the presence of nitrogen to obtain an adjustable FAU / LTA (CuⅠ) zeolite nanocrystal.

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing adjustable FAU / LTA (CuⅠ) zeolite nanocrystals, characterized in that: The following steps are involved: Step 1, fully mix the silicon source: aluminum source: alkali source: water in a molar ratio of 1:0.2-1.2:0.1-4:5-100 to prepare a mixture; Step 2: Under steam-assisted conditions, the mixture is subjected to aging and crystallization treatments in sequence to obtain a crystalline product; Step 3, washing, drying and calcining the crystal product in sequence to obtain FAU / LTA type zeolite nanocrystals; Step 4, mixing the FAU / LTA zeolite nanocrystals and the rare earth metal salt M in a solid phase, and vacuum drying to obtain a solid mixture A containing rare earth elements, wherein the mass ratio of the FAU / LTA zeolite nanocrystals to the rare earth metal salt is 1:0.01-3; Step 5, solid-state grinding the solid mixture A and the cuprous salt, wherein the mass ratio of the FAU / LTA zeolite nanocrystals to the cuprous salt is 1:0.4-1, to obtain a solid mixture B containing the cuprous salt; Step 6: placing the solid mixture B in a tubular furnace and calcining it in the presence of a protective gas to obtain adjustable FAU / LTA (CuⅠ) zeolite nanocrystals.

2. The method for preparing adjustable FAU / LTA (CuⅠ) zeolite nanocrystals according to claim 1, characterized in that: The silicon source in step 1 is one or more of white carbon black, porous silicon, solid silica gel and silica sol; And / or, the aluminum source in step 1 is one or more of aluminum isopropoxide, sodium aluminate, aluminum hydroxide, aluminum chloride and aluminum sulfate; And / or, the alkali source in step 1 is one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, magnesium hydroxide, ammonia water and ethylenediamine.

3. The method for preparing adjustable FAU / LTA (CuⅠ) zeolite nanocrystals according to claim 1, characterized in that: Step 2: Under steam-assisted conditions, the mixture is subjected to aging and crystallization treatments in sequence, which specifically includes the following steps: the mixture is transferred into an open glass container, and the glass container is then transferred into a hydrothermal reactor liner, 1-20 ml of deionized water is added to the reactor liner, and water outside the glass container is prevented from entering the glass container; the mixture is subjected to aging treatment at a temperature of 20 to 70° C. under steam-assisted conditions, and the aging time is 0 to 12 days; the crystallization treatment temperature is 20 to 120° C., and the crystallization time is 0 to 8 days.

4. The method for preparing adjustable FAU / LTA (CuⅠ) zeolite nanocrystals according to claim 1, characterized in that: In step 4, a reducing acid may be added to the solid mixture A, and the mass ratio of the reducing acid to the FAU / LTA (CuⅠ) type zeolite nanocrystals is 0.01-2.4:

1.

5. The method for preparing adjustable FAU / LTA (CuⅠ) zeolite nanocrystals according to claim 4, characterized in that: The reducing acid is one or more of citric acid, oxalic acid, sulfurous acid and phosphorous acid.

6. The method for preparing adjustable FAU / LTA (CuⅠ) zeolite nanocrystals according to claim 1, characterized in that: The rare earth metal salt M in step 4 is one or more of lanthanum nitrate, cerium nitrate, cerium trichloride, lanthanum chloride, cerium acetate and lanthanum acetate.

7. The method for preparing adjustable FAU / LTA (CuⅠ) zeolite nanocrystals according to claim 1, characterized in that: The cuprous salt in step 5 is one or more of cuprous chloride, cuprous bromide, cuprous nitrate, cuprous carbonate, cuprous sulfate and cuprous acetate.

8. The method for preparing adjustable FAU / LTA (CuⅠ) zeolite nanocrystals according to claim 1, characterized in that: The calcination temperature in step 6 is 120-600° C., and the calcination time is 4-36 hours.

9. An adjustable FAU / LTA (CuⅠ) zeolite nanocrystal, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of the adjustable FAU / LTA (CuⅠ) zeolite nanocrystals according to claim 9 in the field of CO adsorbent.

Citation Information

Patent Citations

  • Rare earth element-containing FAU / Cu (I) zeolite nanocrystal and preparation method thereof

    CN115254010A